1992
DOI: 10.1038/ng1192-228
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous stop codon in the lysyl hydroxylase gene in two siblings with Ehlers–Danlos syndrome type VI

Abstract: Ehlers-Danlos syndrome (EDS) is characterized by joint hypermobility, alterations in the skin and additional signs of connective tissue involvement. EDS type VI was the first connective tissue disorder for which a specific defect in collagen metabolism was identified, namely a deficiency of lysyl hydroxylase activity. We now report a homozygous single basepair substitution converting the CGA codon (Arg319) to a TGA termination codon in two siblings with EDS type VI. The healthy parents, who are first cousins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 18 publications
2
53
0
2
Order By: Relevance
“…Furthermore, mutations in PITX2 have also been associated with significantly reduced central corneal thickness in humans and mice [Asai-Coakwell et al, 2006]. Mutations in PLOD1 cause Ehlers-Danlos syndrome type VI (MIM# 130050), a connective tissue disorder characterized by joint hypermobility, skin fragility, and hypotonia with ocular manifestations including microcornea, retinal detachment, and fragility of the globe [Hyland et al, 1992;Yeowell and Walker, 2000]. We have shown that PITX2A and FOXC1 are each capable of independently activating transcription from the PLOD1 and FOXO1 promoters in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mutations in PITX2 have also been associated with significantly reduced central corneal thickness in humans and mice [Asai-Coakwell et al, 2006]. Mutations in PLOD1 cause Ehlers-Danlos syndrome type VI (MIM# 130050), a connective tissue disorder characterized by joint hypermobility, skin fragility, and hypotonia with ocular manifestations including microcornea, retinal detachment, and fragility of the globe [Hyland et al, 1992;Yeowell and Walker, 2000]. We have shown that PITX2A and FOXC1 are each capable of independently activating transcription from the PLOD1 and FOXO1 promoters in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Hyl also serves as acceptor for the attachment of collagenspecific glycans (Schegg et al 2009). Defects of lysyl hydroxylation lead to diseases such as Ehlers-Danlos type-VI (Hyland et al 1992), Bruck syndrome (van der Slot et al 2003), and skeletal dysplasia (Salo et al 2008), demonstrating the biological importance of this post-translational modification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the residual activity of EDSVI cells preferentially directed toward type IV collagen (28) suggests the presence of isoforms for lysyl hydroxylase. The presence of isoforms may also explain our previous observations that cells from an EDSVI patient producing a truncated form of lysyl hydroxylase 1, which lacks the highly conserved carboxyl-terminal portion of the molecule, nevertheless have detectable lysyl hydroxylase activity (13).…”
Section: Lysyl Hydroxylase Isoform (2) 6833mentioning
confidence: 53%
“…The complete cDNA-derived amino acid sequence has been reported for the enzyme from chick (9), human (10,11), and rat (12). The enzyme has also been characterized at the genomic level (7), and the first mutations in the lysyl hydroxylase gene have been characterized in patients with type VI of the Ehlers-Danlos syndrome (EDSVI) 1 (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%